A self-balanced electrochemical model for corrosion of reinforcing steel bar in considering the micro-environments in concrete. (10th September 2020) - Zhang, Guoyi; Tian, Ye; Jin, Xianyu; Zeng, Qiang; Jin, Nanguo; Yan, Dongming; Tian, Zushi
Highlights: An electrochemical model taking oxygen concentration, chloride ions concentration, temperature and humidity into account. A combined diffusion of gas and liquid phase in concrete. Self-balance of macrocell and microcell corrosions. Abstract: Based on the electrochemical mechanism of steel corrosion, an improved electrochemical model was established to numerically simulate the corrosion of reinforcement in concrete under marine environment. The corrosion potential distribution and current density of corroded reinforcement were deduced from the corresponding micro-environments on the surface of steel bar, including oxygen, chloride ions, temperature and relative humidity. The equilibrium of gaseous oxygen and dissolved oxygen in pore solution was considered in the model. And the diffusion of invasion mediums in cement matrix and interfacial transition zone (ITZ) were also taken into account. The anode and cathode areas on the surface of steel bar was determined by the time-varying distribution of chloride ions rather than a fixed ratio to achieve the self-balance between macrocell and microcell corrosion. The simulation results agree well with the experimental data. The numerical analysis indicates that the growth of environmental chloride ions concentration will enhance the non-uniformity of chloride ions distribution, but does not contribute much to the increase of maximum rust layer thickness on steel surface. In the propagation stage of corrosion, oxygen concentration is a key factor in controlling corrosion reactions compared to chloride ions. Moreover, environment temperature has a positive effect on both the range of active areas on surface of steel rebar and rust layer thickness.